Meningkatkan Kebugaran Jasmani Siswa Berbasis Aplikasi High Intensity Interval Training QR Code - Ropik Hidayat (Jurnal Guru Dikmen dan Diksus, 2022)
Distance Learning (PJJ) has the potential to limit physical activity and encourage static behavior, which can reduce physical fitness. Meanwhile, students are required to have physical fitness to be able to fight the dangers of the COVID-19 virus. Physical fitness and immunity during the pandemic can be improved through easy and fun physical exercises using the HIIT QR Code application. The HIIT QR Code application is a student physical exercise guide created using the Smartapps Creator software. The purpose of this study was to determine whether there was an effect of using the HIIT QR Code application on students' physical fitness. This type of research is a quasi-experimental which is given to students of SMAN 1 Kesesi class XII MIPA 3. The research sample is 36 people, consisting of 29 women and 7 men. This exercise is given 12 times using the HIIT QR Code application. The instrument used in this study was the Physical Fitness Test (TKJI) with an age range of 16-19 years. Based on the results of data analysis, the results of the Sig. of 0.001 < 0.05, then H0 is rejected and Ha is accepted. This can be seen from the average post-test result of 16.47 which is greater than the average result of the pre-test of 13.36 or an increase of 3.1 after receiving treatment in the form of giving treatment using the HIIT QR Code application.